Targeting Death Receptor 5 (DR5) for the imaging and treatment of primary bone and soft tissue tumors: an update of the literature - Zakareya Gamie; Anja Krippner-Heidenreich; Craig Gerrand; Kenneth Samora Rankin (Frontiers in Molecular Biosciences)
BackgroundDeath Receptor 5 (DR5) is expressed on the surface of primary bone and soft tissue sarcoma cells, and its activation induces cell death primarily through apoptosis. The combination of DR5 agonists and commonly used chemotherapeutic agents, such as doxorubicin, can promote cell death. Currently, clinical trials are investigating the effectiveness of DR5 activation using new biological agents, such as bi-specific or tetravalent antibodies, in improving the survival of patients with relapsed or refractory cancers. Furthermore, investigations continue into the use of novel combination therapies to enhance DR5 response, for example, with inhibitor of apoptosis protein (IAP) antagonist agents [such as the second mitochondria-derived activator of caspase (SMAC) mimetics] and with immune checkpoint inhibitor anti-programmed death-ligand 1 (anti-PD-L1) or anti-programmed cell death-1 (anti-PD-1) antibodies. Other therapies include nanoparticle-mediated delivery of TRAIL plasmid DNA or TRAIL mRNA and stem cells as a vehicle for the targeted delivery of anti-cancer agents, such as TRAIL, to the tumor.MethodsScoping review of the literature from November 2017 to March 2024, utilizing PubMed and Google Scholar.ResultsNew agents under investigation include nanoTRAIL, anti-Kv10.1, multimeric IgM, and humanized tetravalent antibodies. Developments have been made to test novel agents, and imaging has been used to detect DR5 in preclinical models and patients. The models include 3D spheroids, genetically modified mouse models, a novel jaw osteosarcoma model, and patient-derived xenograft (PDX) animal models. There are currently two ongoing clinical trials focusing on the activation of DR5, namely, IGM-8444 and INBRX-109, which have progressed to phase 2. Further modifications of TRAIL delivery with fusion to single-chain variable fragments (scFv-TRAIL), directed against tumor-associated antigens (TAAs), and in the use of stem cells focus on targeted TRAIL delivery to cancer cells using bi-functional strategies.ConclusionIn vitro, in vivo, and clinical trials, as well as advances in imaging and theranostics, indicate that targeting DR5 remains a valid strategy in the treatment of some relapsed and refractory cancers.